The Role of Digital Financing through Crowdfunding in Supporting Social and Humanitarian Fundraising - Muslim; Agustiani, Mulia; Audryna, Leyryza; Nabilah, Azmi; Setiawan, Anthony; Marliana, Marliana; Marjohan, Masno (International Journal of Economics, Management and Accounting (IJEMA), 2025)
This study aims to analyze the role of digital financing through crowdfunding in supporting social and humanitarian fundraising. The method used is a descriptive qualitative approach through a case study. The findings indicate that kitabisa.com has successfully served as a bridge between donors and beneficiaries by utilizing easily accessible digital technology. Factors influencing the success of campaigns include the strength of the narrative, public trust, transparency in fund usage reporting, and the convenience of digital transactions. The platform also encourages broader public participation in social activities in a faster and more efficient manner. These findings suggest that digital crowdfunding is a relevant alternative financing solution in the digital era, particularly for the social and humanitarian sectors.